Synthesis of titanium silicalite-1 (TS-1) zeolite with high content of Ti by a dry gel conversion method using amorphous TiO2–SiO2 composite with highly dispersed Ti species. (June 2020) - Soekiman, C.N.; Miyake, K.; Hayashi, Y.; Zhu, Y.; Ota, M.; Al-Jabri, H.; Inoue, R.; Hirota, Y.; Uchida, Y.; Tanaka, S.; Kong, C.Y.; Nishiyama, N.
Abstract: In this study, we have developed a new method to synthesize mesoporous titanium silicalite-1 (TS-1) with a higher content of active titanium in the framework (more than 5%) than that obtained from the conventional hydrothermal synthesis. The new method combines two methods as follows: (1) a sol-gel method in tetrahydrofuran for the synthesis of TiO2 –SiO2 composite with highly dispersed Ti species and (2) a dry gel conversion method for the crystallization to TS-1. This investigation revealed that the dispersion of Ti in the starting materials was quite important to synthesize mesoporous TS-1 with high content of Ti besides dry conversion method. The obtained mesoporous TS-1 with a high content of titanium showed higher catalytic activity in 1-hexene epoxidation than conventional TS-1. This high activity is likely to originate from the high content of titanium in the framework. Highlights: Titanium silicalite-1(TS-1) with high content of Ti was synthesized by combining sol-gel method and dry gel conversion method. The state of Ti in the starting materials and crystallization process are crucial to synthesize mesoporous TS-1 with high content of Ti. The TS-1 with high content of Ti showed much high catalytic performance on the epoxidation.